Gobernanza neoliberal. Retos para el ordenamiento de las movilidades urbanas - Calonge Reillo, Fernando (2017)
This paper contributes to consolidate the studies on neoliberal governance in present metropolitan environments, especially in urban mobility. It exposes how neoliberal policy on mobility is formulated through the establishment of public-private partnerships and it shows the resulting perspective on planning. The paper offers a final analysis on social exclusion and urban fragmentation phenomena derived from this neoliberal articulation of urban mobility policy.